1993
DOI: 10.1182/blood.v81.3.793.793
|View full text |Cite
|
Sign up to set email alerts
|

Dye-mediated photolysis is capable of eliminating drug-resistant (MDR+) tumor cells

Abstract: We evaluated the potential role of photoradiation therapy with a benzoporphyrin derivative, monoacid ring A (BPD-MA), and dihematoporphyrin ether (DHE), for the ex vivo purging of residual tumor cells from autologous bone marrow (BM) grafts. BPD-MA and DHE photosensitizing activity was tested against two human large-cell lymphoma cell lines and colony-forming unit-leukemia (CFU-L) derived from patients with acute myelogenous leukemia (AML). In mixing experiments, 4-log elimination of tumor cell lines was obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…As shown, BPD-MA ha5 relatively little effect upon stem cells in vitm. However, the efficacy of BPD-MA against multidrug-resistant cells is low when compared to Photofrin@ (51). At the concentration of BPD-MA that killed 100% OCI-MY7, over 90% of stem cells (CD34') cells survived.…”
Section: Discussionmentioning
confidence: 99%
“…As shown, BPD-MA ha5 relatively little effect upon stem cells in vitm. However, the efficacy of BPD-MA against multidrug-resistant cells is low when compared to Photofrin@ (51). At the concentration of BPD-MA that killed 100% OCI-MY7, over 90% of stem cells (CD34') cells survived.…”
Section: Discussionmentioning
confidence: 99%
“…One potential advantage of photodynamic purging of hemopoietic cell: with PHOTOFRIN@ was pointed out by Lemoli et al [20]. They showed that the presence of the multidrug resistance marker (MDR') on two human leukemic cell lines (HL-60/RV and CEM/VBL) did not increase their resistance to PDT with PHOTOFRIN@.…”
Section: Photofrin@mentioning
confidence: 99%
“…Similar selectivity with B P D was noted in experiments comparing normal progenitor survival with survival of leukemic blast progenitors from patients with AML. In these studies, in which medium contained 1% fetal calf serum (FCS) at all times, a 3 log reduction (limit of detection) was seen under conditions in which fewer than 50% of normal progenitors were eliminated [20].…”
Section: Benzoporphyrin Derivative Monoacid Ring a (Bpd)mentioning
confidence: 99%